Volume 1: Turbomachinery 1994
DOI: 10.1115/94-gt-363
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tip Clearance on a Swept Transonic Compressor Rotor

Abstract: An experimental and numerical investigation of detailed tip clearance flow structures and their effects on the aerodynamic performance of a modern low-aspect-ratio, high-through-flow, axial transonic fan is presented. Rotor flow fields were investigated at two clearance levels experimentally, at tip clearance to tip blade chord ratios of 0.27 and 1.87 percent, and at four clearance levels numerically, at ratios of zero, 0.27, 1.0, and 1.87 percent. The numerical method seems to calculate the rotor aerodynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…This was fed by radial outward flow along the suction surface. Rather similar features were noted by Copenhaver et al [5] on a Wright Research Laboratory aft-swept rotor, and by Hah and Rabe [6] on the first rotor of the two-stage ADLARF fan. These studies employed considerably finer grids with six to ten cells across the tip gap as opposed to only two.…”
Section: Rotor Tip Issuessupporting
confidence: 80%
“…This was fed by radial outward flow along the suction surface. Rather similar features were noted by Copenhaver et al [5] on a Wright Research Laboratory aft-swept rotor, and by Hah and Rabe [6] on the first rotor of the two-stage ADLARF fan. These studies employed considerably finer grids with six to ten cells across the tip gap as opposed to only two.…”
Section: Rotor Tip Issuessupporting
confidence: 80%
“…Through the aerodynamic bene ts gained, the swept blade came of age in the mid-1980s as a concept to develop a low aspect ratio, ef cient, transonic rotor for aeroengine compression systems. In this ambit, a huge amount of work dealt with rotor aerodynamics [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Copenhaver et al [1] combined experimental and computational approaches to study the effect of tip clearance variation on efficiency for a swept, transonic compressor rotor. Sakulkaew et al [2] performed a computational study on efficiency and found that an optimum tip clearance existed for which the combined, competing effects of tip leakage flow rate and tip leakage mixing loss minimized overall loss.…”
Section: Introductionmentioning
confidence: 99%